ASSESSING UNIVERSITY TECHNOLOGY TRANSFER: A MEASURE OF EFFICIENCY PATTERNS - KIM, JISUN; ANDERSON, TIMOTHY; DAIM, TUGRUL (International Journal of Innovation and Technology Management (IJITM), 2008)
There have been very active and significant studies done in the area of university technologies transfer (UTT). One interested topic among them is to measure performance of the UTT. Data Envelopment Analysis (DEA) has been regarded as a proper approach to measure the university technology transfer efficiency (UTTE). However, current studies stay in identifying efficient and inefficient universities and related output or input variables which could contribute to improve their efficiencies. This study is intended to understand further how the universities recognized efficient are different and the changes of their performance over years. For this purpose, this study proposes a new approach, the efficiency pattern diagram, to identify changing patterns of the technology transfer of 17 efficient universities out of 51 US universities from 2001 to 2004. Five efficiency patterns are identified by this study: "newly emerging", "strengthening", "strong", "weakening", and "declining". The properties of each pattern and limitations of the approach are discussed with verification of the pattern by extending them to 2005.